Impaired IKs channel activation by Ca2 +-dependent PKC shows correlation with emotion/arousal-triggered events in LQT1. (February 2015) - O-Uchi, Jin; Rice, J. Jeremy; Ruwald, Martin H.; Parks, Xiaorong Xu; Ronzier, Elsa; Moss, Arthur J.; Zareba, Wojciech; Lopes, Coeli M.
Abstract: Background: The most common inherited cardiac arrhythmia, LQT1, is due to IKs potassium channel mutations and is linked to high risk of adrenergic-triggered cardiac events. We recently showed that although exercise-triggered events are very well treated by ß-blockers for these patients, acute arousal-triggered event rate were not significantly reduced after beta-blocker treatment, suggesting that the mechanisms underlying arousal-triggered arrhythmias may be different from those during exercise. IKs is strongly regulated by β-adrenergic receptor (β-AR) signaling, but little is known about the role of α1-AR-mediated regulation. Methods and results: Here we show, using a combination of cellular electrophysiology and computational modeling, that IKs phosphorylation and α1-AR regulation via activation of calcium-dependent PKC isoforms (cPKC) may be a key mechanism to control channel voltage-dependent activation and consequently action potential duration (APD) in response to adrenergic-stimulus. We show that simulated mutation-specific combined adrenergic effects (β + α) on APD were strongly correlated to acute stress-triggered cardiac event rate for patients while β-AR effects alone were not. Conclusion: We were able to show that calcium-dependent PKC signaling is key to normal QT shortening during acute arousal and when impaired, correlates with increased rate of sudden arousal-triggered cardiac events. Our study suggests that the acute α1-AR-cPKC regulation of IKs is important for QT shortening in "fight-or-flight" response and is linked to decreased risk of sudden emotion/arousal-triggered cardiac events in LQT1 patients. Highlights: α1 -AR-cPKC activates KCNQ1/KCNE1 independently of β-AR-mediated activation. α1 -AR-cPKC-E1(S102) activates KCNQ1/KCNE1 by shifting V1/2 of channel activation. Simulated mutant PKC + PKA APD effects correlates to acute arousal events in LQT1. α1 -AR-cPKC-E1(S102) is important for shortening of APD at high adrenergic states. Data may explain lower rate of acute arousal than exercise triggers for LQT1.